2017
DOI: 10.1038/s41598-017-06462-y
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Genetic Analyses in the Diagnosis of Tetrahydrobiopterin (BH4)-Responsiveness in Chinese Phenylalanine Hydroxylase Deficiency Patients

Abstract: Molecular characterization of PAH deficiency has been proven essential in establishing treatment options. We examine the diagnostic accuracy of two genetic assays to predict BH4 responsiveness: to determine whether the AV sum test or mutation-status assessment test can obviate the need for BH4 loading in Chinese patients. The overall predicted response in 346 patients was 31.65% by the AV sum test and 25.43% by the other assay; both percentages were lower than 51.06% derived from loading results in 94 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…There are also important features to be considered from genotypes when deciding which BH 4 loading test to be used in our particular patient population. The usual 24 or 48‐hr BH 4 loading test may not be adequate for patients that have two nonresponsive alleles or a nonresponsive genotype as they have a higher probability of being slow responders and need a longer period for this BH 4 slow‐responsiveness to be observed (Zhu et al., ). A total of 35 (34.3%) patients in this study could be included in this category.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also important features to be considered from genotypes when deciding which BH 4 loading test to be used in our particular patient population. The usual 24 or 48‐hr BH 4 loading test may not be adequate for patients that have two nonresponsive alleles or a nonresponsive genotype as they have a higher probability of being slow responders and need a longer period for this BH 4 slow‐responsiveness to be observed (Zhu et al., ). A total of 35 (34.3%) patients in this study could be included in this category.…”
Section: Discussionmentioning
confidence: 99%
“…PAH genotyping and genotype‐phenotype association studies may be employed as a screening tool for BH 4 responsiveness, considering the high cost of the drug sapropterin—annual costs for a 29 kg patient were estimated at Can$24,000–Can$72,000 (CADTH Common Drug Reviews, ), especially in low‐resource settings, like Brazil (National Committee for Technology Incorporation—CONITEC, ) and China (Zhu et al., ). Additionally, the accessibility to the drug is limited due to the decision of several health technology assessment agencies not to reimburse it, including the National Committee for Technology Incorporation (CONITEC) recommendation to fund it through the Brazilian Public Health System—SUS only for women in the preconception period and during pregnancy (National Committee for Technology Incorporation—CONITEC, ).…”
Section: Discussionmentioning
confidence: 99%
“…Zurfluh et al (2008) proposed that mild PKU phenotypes have a better response on BH4-supplementation [33], which was later supported by subsequent studies [30,31,34,35,36,37]. Zhu et al (2017) found out that 89.58% of BH4-responders had mild phenotypes and the remaining 10.42% were presented with cPKU [38]. Although knowing the patient’s complete genotype is considered to be the BH4-responsiveness predictor [39], the interallelic complementation appears to affect the resultant phenotype and response on BH4-supplementation [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with hyperphenylalaninemia (HPA) experience a depletion of catecholamines and serotonin because BH4 is a necessary cofactor for PAH, tyrosine-3-hydroxylase, and tryptophan-5-hydroxylase in addition to all three isoforms of nitric oxide synthase (NOS), the key enzymes in the biosynthesis of dopamine and serotonin [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%